2013
DOI: 10.1016/j.jacc.2012.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Cardiospheres Safely Boost Cardiac Function and Attenuate Adverse Remodeling After Myocardial Infarction in Immunologically Mismatched Rat Strains

Abstract: Allogeneic cardiospheres increase viable myocardium, decrease scar, improve function, and attenuate adverse remodeling in the infarcted rat heart, without deleterious immunological sequelae. These observations lay the groundwork for developing cardiospheres as a novel off-the-shelf microtissue product for myocardial regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 37 publications
5
79
0
3
Order By: Relevance
“…Cardiosphere-derived cells (CDCs) (26) are a unique heartderived cell type that confers functional and structural benefits, including reduction of infarct size, improvement of cardiac function, enhanced angiogenesis, and modulation of the inflammatory response after MI (27)(28)(29)(30)(31). Recently, in a porcine model, we have found that CDCs are able to confer acute cardioprotection when administered 30 minutes after IR (a phenomenon called "cellular postconditioning"; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiosphere-derived cells (CDCs) (26) are a unique heartderived cell type that confers functional and structural benefits, including reduction of infarct size, improvement of cardiac function, enhanced angiogenesis, and modulation of the inflammatory response after MI (27)(28)(29)(30)(31). Recently, in a porcine model, we have found that CDCs are able to confer acute cardioprotection when administered 30 minutes after IR (a phenomenon called "cellular postconditioning"; ref.…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, allogeneic CDC transplantation without immunosuppression induces only a transient mild local immune reaction in a rat myocardial infarction (MI) model. [10][11] The CADUCEUS (CArdiosphere-Derived aUtologous Stem CElls to Reverse ventricUlar dySfunction) trial proved the efficacy and safety of CDC transplantation for treatment of MI. 12 Recently, Mohammad et al found that CDC treatment prevents functional deterioration, attenuates oxidative stress, promotes cardiomyocyte proliferation, and reduces mortality in a transgenic mouse model of dilated cardiomyopathy (DCM).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our phenotyping ended 2 months after cell treatment in this study. Although our previous work indicates that the benefits of CDCs can last even longer,10, 14 more‐extended evaluation would be valuable, particularly in terms of hard clinical endpoints, such as progression to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 3 to 5 sections obtained from the border zones were evaluated per heart with immunostaining for Isolectin (Invitrogen I21411; Invitrogen, Carlsbad, CA) and α‐smooth muscle actin (α‐SMA; ab5694; Abcam). Masson's trichrome staining (Sigma‐Aldrich, St. Louis, MO) was performed on serial sections for tissue collagen quantification 10. To measure apoptotic cardiomyocytes, sections from myocardial samples underwent immunostaining for terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL; Roche 12156792910; Roche, Indianapolis, IN) and α‐sarcomeric actinin (ab9465; Abcam).…”
Section: Methodsmentioning
confidence: 99%